Penerapan Model Picture and Picture untuk meningkatkan aktivitas dan hasil belajar IPA pada materi Penggolongan Hewan dan tumbuhan di kelas III MIN 8 Aceh Barat Daya - Linarmawati, Linarmawati (Jurnal Pendidikan dan Pengabdian Vokasi (JP2V), 2020)
The title of this research is "The Application of Picture and Picture Models to Improve Activities and Learning Outcomes of Natural Sciences in Classification of Animal and Plant Material in Class III MIN 8 Southwest Aceh Academic Year 2018/2019". The problem in this study is that students' mastery of science lessons is still low. The purpose of this class action research is to find out (1) Improvement of student learning outcomes after the application of the Picture and Picture model (2) The activities of the teacher and students in learning the Picture and Picture model. This study uses a class action research (Action Reseach) of two cycles. Each cycle consists of four stages: design, activity and observation, re-flection. This research was conducted from October to November 2018. The subjects of this study were class III students totaling 29 students. The research approach was carried out using the descriptive ap-proach method. Data collection techniques are done using tests, observation is the observation of teacher activities and student activities. Data processing and analysis is used by using percentage techniques. Based on calculations and data analysis in this study shows that student learning outcomes have in-creased ie from the first cycle which initially only 72.41% increased 86.21% cycle II. The results of the analysis of teacher activity have increased from the first cycle to 60.95% (Good Enough) and increased in the second cycle to 86.67% (Very good). The results of the analysis of student activity have increased from cycle I 62.86% (Good) and increased in cycle II which is 85.71% (Very good), so it can be con-cluded that the application of picture and picture models can improve student learning outcomes in class III, as well as this learning model can be used as an alternative to science learning.